Professional Performance Of Health Establishments With Obstetric-neonatal Functions Of Lima and Province Of 2015 - Bances Dávalos, Luz Elena (2021)
Objective: To compare the professional performance of the health establishments with essential obstetric and neonatal functions from Lima with respect provincie during September-October of 2015. Materials and methods: It´s a cross- sectional analytical investigation conducted in 350 health establishments with essential obstetric-neonatal functions I-II (FONE I-II) database based on national surveys conducted by the National Institute of Statistics and Informatics (INEI) during 2015. New variables were created from the databases to determinate the gynecology staff´s professional performance and analyzed the data with the R statistical software and the IBM SPSS Statistics 25 using the chi-square test. Results: The investigation showed that midwifes were the healthl staff who most frequently attended vaginal births, both in Lima (62.9%) and in provinces (91.4%). With respect to the partogram, only 5% of the establishments in Lima and 4% of the establishments in the provinces fully registered the partogram. Significant difference in professional performance was found during the vaginal delivery (p= 0.008) and the third stage of labor (p= 0.014). Similarly, we found significant differences in the late cord clamping (p = 0.002) between Lima and provinces. The average clamping time was 2 minutes 30 seconds in both cases and on skin-to-skin contact; it was 13 minutes for Lima and 10 minutes for provinces. Conclusions: There is a gap in professional performance during vaginal delivery care between the FONE I-II establishments in Lima and provinces. Nationally there are still deficits in compliance with the indicators to achieve adequate attention.